Integrated analysis of O/K-antigen biosynthesis diversity and molecular serotyping scheme development of Vibrio alginolyticus - Keyi Yu; Zhenzhou Huang; Yanjun Li; Lizhi Ma; Xuemei Bai; Xiuping Fu; Biao Kan; He Gao (BMC Microbiology)
Abstract Vibrio alginolyticus is a foodborne pathogen that poses considerable threats to human health and leads to substantial economic losses in the aquaculture industry. O and K antigen are bacterial surface structures with strong plasticity and environmental adaptability, making O antigen biosynthesis gene clusters (O-AGCs) and K antigen biosynthesis gene clusters (K-AGCs) good materials for studying bacterial genetic evolution. However, no studies have carried out in-depth analyses of the O and K antigen-related gene clusters of V. alginolyticus. In the present study, we conducted the first genome-based serogroup study of V. alginolyticus and performed a comprehensive analysis of the O- and K-AGCs. We elucidated their molecular evolutionary mechanism by comparing them at the whole gene cluster structural and molecular levels. There were 14 serotypes of O-AGCs between dgkA and gmhD and 48 serotypes of K-AGCs between gmhD and rjg among V. alginolyticus chromosomes. Serogroups O1, O4, and O11 were most prevalent in our sample set, accounting for approximately 60% of all V. alginolyticus strains. The K serogroups had more extensive diversity than the O serogroups. We further identified the K serogroup-specific gene, wzy, corresponding to the serogroup in a one-to-one parallel relationship. The variation in K antigen, distinguished by the unique sequence of the gene wzy, makes an essential contribution to the diagnostic investigations of V. alginolyticus. Our results represent the first insight into the O and K antigen diversity of V. alginolyticus and underline the importance of the structural versatility and functional adaptability of O- and K-AGCs.